Current surgical treatment standards for esophageal and esophagogastric junction cancer. Issue 1 (14th August 2020) - Jung, Minoa K.; Schmidt, Thomas; Chon, Seung‐Hun; Chevallay, Mickael; Berlth, Felix; Akiyama, Junichi; Gutschow, Christian A.; Mönig, Stefan P.
Abstract: A number of different surgical techniques for the treatment of cancer of the esophagus and the esophagogastric junction have been proposed. Guidelines generally recommend a transthoracic approach for esophageal cancer, including Siewert type I tumors. In tumors of the proximal esophageal third, transthoracic esophagectomy may be extended to a three‐field approach, including resection of cervical lymph nodes. However, the choice between transthoracic esophagectomy with intrathoracic anastomosis (Ivor Lewis esophagectomy) and the three‐incision approach with cervical esophago‐gastrostomy (McKeown esophagectomy) remains controversial, with guidelines varying among different countries. Furthermore, it is commonly accepted that Siewert type III tumors should be treated by extended total gastrectomy with transhiatal resection of the lower esophagus, whereas currently no consensus exists regarding the optimal surgical approach for the treatment of Siewert type II adenocarcinoma. Likewise, there is a major controversy regarding palliative and potentially curative treatment modalities in oligometastatic disease. This review deals with current surgical treatment standards for cancer of the esophagus and the eosphagogastric junction, including discussion of ongoing trials. Abstract : A number of different surgical techniques for the treatment of cancer of the esophagus and the esophagogastric junction have been proposed. This review deals with current surgical treatment standards for cancer of the esophagus and the eosphagogastric junction, including discussion of ongoing trials.